When the final whistle blows: Social identity pathways support mental health and life satisfaction after retirement from competitive sport. (November 2021) - Haslam, Catherine; Lam, Ben C.P.; Yang, Jie; Steffens, Niklas K.; Haslam, S. Alexander; Cruwys, Tegan; Boen, Filip; Mertens, Niels; De Brandt, Koen; Wang, Xinyan; Mallett, Clifford J.; Fransen, Katrien
Abstract: For many athletes, retirement from higher levels of competitive sport poses significant challenges. Research has shown that athletic identity is a key predictor of adjustment trajectories, but the mechanisms through which this affects outcomes are less clear. Added to this, there has been limited research on the role that wider social identities, and the resources they enable, play in adjustment. Addressing both these issues, we examined theoretically derived social identity pathways to retirement adjustment in athletes who had played sport at higher competitive levels and two potential mechanisms, or psychological resources, through which adjustment might be enabled. This was examined in two samples: retired athletes from countries in Western ( n = 215) and Eastern ( n = 183) regions. Loss of athletic identity, social group memberships (multiple, maintained and new), psychological resources (perceived meaning in life and control), and adjustment (life satisfaction, depression, and perceived physical health) were assessed. In both samples, the loss of athletic identity undermined adjustment by reducing meaning in life and perceived control. Path analysis showed that both maintained and gained social group memberships counteracted the negative effects of athletic identity loss on adjustment. Evidence that these pathways enabled access to psychological resources was found primarily in Chinese athletes, with maintained groups influencing personal control and new groups influencing meaning in life. These findings highlight the importance of social identity processes to retirement from higher levels of competitive sport and the mechanisms through which they can either support or undermine adjustment. Highlights: Athletic identity loss undermines adjustment to elite sport retirement. Such loss reduced athletes' meaning in life and perceived control. Groups gained and maintained counteracted negative effects of identity loss. Social group processes were associated with greater meaning in life and control.